Impacts of nitrogen addition on plant species richness and abundance: A global meta‐analysis. Issue 3 (13th December 2018) - Midolo, Gabriele; Alkemade, Rob; Schipper, Aafke M.; Benítez‐López, Ana; Perring, Michael P.; De Vries, Wim
Abstract: Aim: Experimental nitrogen (N) addition (fertilization) studies are commonly used to quantify the impacts of increased N inputs on plant biodiversity. However, given that plant community responses can vary considerably among individual studies, there is a clear need to synthesize and generalize findings with meta‐analytical approaches. Our goal was to quantify changes in species richness and abundance in plant communities in response to N addition across different environmental contexts, while controlling for different experimental designs. Location: Global. Time period: Data range: 1985–2016; Publication years: 1990–2018. Major taxa studied: Plants. Methods: We performed a meta‐analysis of 115 experiments reported in 85 studies assessing the effects of N addition on terrestrial natural and semi‐natural plant communities. We quantified local‐scale changes in plant biodiversity in relationship to N addition using four metrics: species richness (SR), individual species abundance (IA), mean species abundance (MSA) and geometric mean abundance (GMA). Results: For all metrics, greater amounts of annual N addition resulted in larger declines in plant diversity. Additionally, MSA decreased more steeply with N that was applied in reduced (NH4 + ) rather than oxidized ( NO 3 - ) form. Loss of SR with increasing amounts of N was found to be larger in warmer sites. Furthermore, greater losses of SR were found in sites with longer experimental durations, smaller plot sizes and lower soil cation exchange capacity. Finally, reductions in the abundance of individual species were larger for N‐sensitive plant life‐form types (legumes and non‐vascular plants). Main conclusions: N enrichment decreases both SR and abundance of plants in N‐addition experiments, but the magnitude of the response differs among biodiversity metrics and with the environmental and experimental context. This underlines the importance of integrating multiple dimensions of biodiversity and relevant modifying factors into assessments of biodiversity responses to global environmental change.